Increase of microRNA-210, decrease of raptor gene expression and alteration of mammalian target of rapamycin regulated proteins following mithramycin treatment of human erythroid cells. - Nicoletta Bianchi; Alessia Finotti; Manuela Ferracin; Ilaria Lampronti; Cristina Zuccato; Giulia Breveglieri; Eleonora Brognara; Enrica Fabbri; Monica Borgatti; Massimo Negrini; Roberto Gambari (PLoS ONE)
Expression and regulation of microRNAs is an emerging issue in erythroid differentiation and globin gene expression in hemoglobin disorders. In the first part of this study microarray analysis was performed both in mithramycin-induced K562 cells and erythroid precursors from healthy subjects or β-thalassemia patients producing low or high levels of fetal hemoglobin. We demonstrated that: (a) microRNA-210 expression is higher in erythroid precursors from β-thalassemia patients with high production of fetal hemoglobin; (b) microRNA-210 increases as a consequence of mithramycin treatment of K562 cells and human erythroid progenitors both from healthy and β-thalassemia subjects; (c) this increase is associated with erythroid induction and elevated expression of γ-globin genes; (d) an anti-microRNA against microRNA-210 interferes with the mithramycin-induced changes of gene expression. In the second part of the study we have obtained convergent evidences suggesting raptor mRNA as a putative target of microRNA-210. Indeed, microRNA-210 binding sites of its 3'-UTR region were involved in expression and are targets of microRNA-210-mediated modulation in a luciferase reporter assays. Furthermore, (i) raptor mRNA and protein are down-regulated upon mithramycin-induction both in K562 cells and erythroid progenitors from healthy and β-thalassemia subjects. In addition, (ii) administration of anti-microRNA-210 to K562 cells decreased endogenous microRNA-210 and increased raptor mRNA and protein expression. Finally, (iii) treatment of K562 cells with premicroRNA-210 led to a decrease of raptor mRNA and protein. In conclusion, microRNA-210 and raptor are involved in mithramycin-mediated erythroid differentiation of K562 cells and participate to the fine-tuning and control of γ-globin gene expression in erythroid precursor cells.